Silicon particle, silicon-containing active material, negative electrode active material for secondary batteries, negative electrode and secondary battery
By employing silicon particles with a high (111) plane orientation and a specific BET surface area, along with a silicon-oxygen-carbon matrix, the cycle characteristics of lithium ion secondary batteries are enhanced, addressing the breakdown issues of silicon-based electrodes and improving battery longevity.
Patent Information
- Application Number
- JP2023111508
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-06
- Publication Date
- 2025-01-20
AI Technical Summary
Existing silicon-based negative electrode active materials for lithium ion secondary batteries suffer from poor cycle characteristics due to the breakdown of silicon particles during repeated charging and discharging, which is exacerbated by the large volume expansion and contraction of silicon when lithium is absorbed and released.
The use of silicon particles with a high degree of orientation of the (111) plane, a specific BET surface area, and a controlled crystallite diameter, combined with a matrix phase containing silicon, oxygen, and carbon, to form a silicon-containing active material that reduces stress on the matrix phase and enhances cyclability.
The proposed silicon-containing active material significantly improves the cycle life and cyclability of lithium ion secondary batteries by minimizing the breakdown of active material during charging and discharging, maintaining structural integrity and enhancing electrochemical performance.
Smart Images

Figure 2025008898000001 
Figure 2025008898000002 
Figure 2025008898000003
Abstract
Description
[Technical field]
[0001] The present invention relates to silicon particles and a silicon-containing active material containing the silicon. The present invention also relates to a negative electrode active material for a secondary battery containing the silicon-containing active material, a negative electrode containing the negative electrode active material for a secondary battery, and a secondary battery containing the negative electrode. [Background technology]
[0002] Non-aqueous electrolyte secondary batteries are used in portable devices, hybrid and electric vehicles, home storage batteries, and the like, and are required to have a good balance of multiple properties such as electric capacity, safety, and operational stability. Furthermore, in recent years, with the miniaturization of various electronic devices and communication devices and the rapid spread of hybrid automobiles and the like, there has been a strong demand for the development of lithium ion secondary batteries that have higher capacity and further improved various battery characteristics, such as cycle characteristics and discharge rate characteristics, as a driving power source for these devices and the like.
[0003] Since silicon has a large theoretical electric capacity, its use as an anode active material has been considered for the purpose of increasing the capacity of lithium-ion secondary batteries. However, silicon has a large difference between the volume expansion when it absorbs lithium and the volume contraction when it releases it, and silicon particles are destroyed during repeated charging and discharging. As a result, secondary batteries using silicon as an anode active material have inferior cycle characteristics.
[0004] For the purpose of improving the cycle characteristics of a secondary battery using silicon as a negative electrode active material, for example, Patent Document 1 proposes a specific silicon or silicon alloy having an average particle size (D50), an average particle size (D90), a BET specific surface area by the BET method, and an oxygen content each falling within a specific range.
[0005] Patent Document 2 proposes a negative electrode active material that is made of silicon particles having specific surface conditions, sizes, shapes, etc., and a silicon-based inorganic compound that encapsulates the silicon particles, and has a specific chemical bond state of the silicon element. It has been shown that a secondary battery using such a negative electrode active material simultaneously exhibits high levels of charge / discharge capacity, initial coulombic efficiency, and cycle characteristics. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2021-180124 A [Patent Document 2] JP 2021-114483 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, even in the active material for secondary batteries described in Patent Document 1, repeated charging and discharging caused particle destruction and the cycle characteristics were insufficient. Although the cycle characteristics were improved in Patent Document 2, further improvement in the cycle characteristics is being demanded due to the recent increasing demand for performance in secondary battery applications. Therefore, there is a demand for the development of an active material for lithium secondary batteries using silicon particles and having improved cycle characteristics.
[0008] The present inventors have investigated active materials for secondary batteries having excellent cycle characteristics by focusing on the shape of silicon particles, particularly the crystal planes of silicon particles, and have found silicon particles that provide active materials for secondary batteries having excellent cycle characteristics for lithium secondary batteries. That is, an object of the present invention is to provide silicon particles for use as an active material for a secondary battery having excellent cycle characteristics. [Means for solving the problem]
[0009] The present invention has the following aspects. [1] Silicon particles having a degree of orientation of the (111) plane, F(111), of 0.2 or more, as determined by the Lotgering method in X-ray diffraction. [2] BET specific surface area is 80m 2 / g or more. [3] The silicon particles according to [2], having a crystallite diameter calculated by the Scherrer method of 5 nm or more and 14 nm or less.
[0010] The present invention also has the following aspects. [4] A silicon-containing active material comprising the silicon particles according to any one of [1] to [3] above. [5] The silicon-containing active material according to [4], wherein the degree of orientation, F(111), of the (111) plane of silicon particles obtained by the Lotgering method in X-ray diffraction of the silicon-containing active material is 0.03 or more. [6] BET specific surface area is 50m 2 / g or less of the silicon-containing active material according to [4] or [5]. [7] The silicon-containing active material according to any one of [4] to [6] above, having a volume average particle size of 2 μm or more and 20 μm or less. [8] The silicon-containing active material according to any one of [4] to [7], wherein the silicon crystallite size in the silicon-containing active material is 40 nm or less. [9] The silicon-containing active material according to any one of [4] to [8], which contains a matrix phase containing silicon, oxygen, and carbon as main components.
[0011] Further, the present invention has the following aspects.
[10] A negative electrode active material for a secondary battery, comprising the silicon-containing active material according to any one of [4] to [9].
[11] A negative electrode comprising the negative electrode active material for a secondary battery according to
[10] .
[12] A secondary battery comprising the negative electrode according to
[11] . Effect of the Invention
[0012] According to the present invention, there is provided an active material for a secondary battery used in a lithium ion secondary battery, and a secondary battery containing the active material for a secondary battery as a negative electrode active material, which provides a secondary battery with excellent cycleability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The silicon particles of the present invention (hereinafter also referred to as "the present silicon particles") have a degree of orientation of the (111) plane, F(111), of 0.2 or more, as determined by X-ray diffraction (hereinafter also referred to as XRD) using the Lotgering method. The Rod-Gehring method is a method for evaluating the degree of orientation using the Rod-Gehring factor, which is one of the indices that express the degree of orientation of a ceramic polycrystalline body. The Rod-Gehring factor is expressed by the following formula (1), and indicates 1 in the case of perfect orientation.
number
number
[0014] Normally, all silicon particles are randomly oriented, with an orientation degree of approximately 0. This is considered to be a state in which there are almost no planes on which crystals have developed. It is known that in the case of active materials that have silicon particles and a matrix phase, stress on the matrix phase increases with expansion and contraction as lithium penetrates and is released from the silicon particles during charging and discharging of a lithium secondary battery. It is believed that this increase in stress makes the matrix phase more susceptible to destruction, and ultimately the collapse of the active material. As a result, it is believed that the cycle life of a lithium secondary battery using silicon particles is shortened, and the cyclability is reduced.
[0015] On the other hand, the present silicon particles are highly oriented in the (111) plane, with a degree of orientation of 0.2 or more, and the crystals of the present silicon particles are particles in which the (111) plane is developed. Therefore, the area of the (111) surface of the silicon particles in the active material is large, and it is considered that the stress in the vertical direction of the (111) surface is small when lithium penetrates into and is released from the silicon particles during charging and discharging of a lithium secondary battery. As a result, it is considered that when the silicon particles are used as an active material, the collapse of the active material can be suppressed. It is also considered that the collapse of the active material can be suppressed by controlling the matrix with the silicon particles. It is believed that this improves the cycle life and cyclability of the lithium secondary battery. From the above viewpoint, the orientation degree of the (111) plane of the present silicon particles, F(111), is preferably 0.2 or more from the viewpoint of relatively reducing the stress on the matrix phase even in the case of an active material having a matrix phase, and suppressing the destruction of the matrix phase, and more preferably 0.4 or more. Also, F is 1 or less as described above.
[0016] The BET specific surface area of this silicon particle is 80m 2 / g or more is preferable from the viewpoint of electric capacity and initial coulombic efficiency. The BET specific surface area is a value determined by the BET method, and can be determined by nitrogen gas adsorption measurement, for example, by using a BET specific surface area measuring device. The BET specific surface area of the silicon particles is in the range of 80 to 300 m from the viewpoint of capacitance and initial coulombic efficiency. 2 / g is more preferable, and 100 to 230m 2 / g is more preferred.
[0017] From the viewpoint of initial coulombic efficiency and capacity retention, it is preferable that the crystallite diameter (hereinafter, also referred to as "crystallite diameter") calculated by the Scherrer method from the diffraction peak assigned to the (111) plane in the XRD of the present silicon particle is 5 nm or more and 14 nm or less. The crystallite diameter is more preferably 12 nm or less, and further preferably 11 nm or less. The Scherrer method is a method for determining the crystallite diameter from powder XRD. The crystallite size, L, is expressed by the following formula (3) when the peak angle, θ, from the powder XRD and its half-width, β, are expressed as follows: L = Kλ / (βcosθ) (3) In equation (3), K is the Scherrer constant, which is usually set to 0.9, and λ is the wavelength of the X-rays used in the XRD.
[0018] The particle size of the silicon particles is preferably nano-order in volume average particle size. Small particle size improves cycle performance. The volume average particle size of the nano order means that the volume average particle size is in nanometer units, and the volume average particle size is usually 1 to 999 nm. If the silicon particles exceed 1000 nm, the dispersibility of the silicon particles when they are made into a silicon slurry for producing an active material may deteriorate, and the productivity may decrease. From these viewpoints, the volume average particle size of the silicon particles is preferably 10 to 150 nm, more preferably 10 to 100 nm, and even more preferably 20 to 70 nm. The volume average particle size is the value of D50, which can be measured using a laser diffraction particle size analyzer or the like. D50 can be measured by dynamic light scattering using a laser particle size analyzer or the like. The volume average particle size of the present silicon particles is the particle size at which the cumulative volume distribution curve is drawn from the small diameter side in the particle size distribution, and the particle size at which the cumulative volume distribution curve is 50% is the average particle size.
[0019] The silicon particles may contain oxygen atoms. When the silicon particles contain oxygen atoms, the amount of oxygen atoms in the silicon particles is preferably 5 to 45 atm% relative to silicon atoms from the viewpoints of cycle performance, initial coulombic efficiency, and capacity retention rate when the silicon particles are used as a negative electrode active material of a secondary battery. When the silicon particles contain oxygen atoms, the amount of oxygen atoms in the silicon particles is preferably 5 to 30 atm%, more preferably 5 to 25 atm%, and even more preferably 5 to 15% from the viewpoints of initial coulombic efficiency and capacity retention. The amount of oxygen atoms can be measured by calcining the silicon particles at a temperature of 300 to 800° C. to volatilize the additives, and then performing composition analysis using SEM-EDS (JEOL, JSM-7900F). The silicon particles may contain carbon atoms and nitrogen atoms in addition to silicon atoms and the oxygen atoms. When nitrogen atoms are contained, the amount of nitrogen is preferably 5 mass % or less from the viewpoint of the capacity reduction due to the formation of silicon nitride.
[0020] The shape of the present silicon particles may be any of granular, needle-like, and flake-like as long as the F(111) value of the present silicon particles is within the above range, but from the viewpoint of charge / discharge performance when used as a negative electrode active material, a flake-like shape is preferred. From the viewpoint of charge / discharge performance when used as a negative electrode active material, the silicon particles preferably have a length in the long axis direction of 30 to 300 nm and a thickness of 1 to 60 nm. From the viewpoint of charge / discharge performance when used as a negative electrode active material, the silicon particles preferably have a needle-like or flake-like shape with an aspect ratio, which is the ratio of length to thickness, of 0.5 or less.
[0021] The morphology of the silicon particles can be measured by the average particle size using a dynamic light scattering method, but samples with the above aspect ratios can be identified more easily and precisely by using analytical means such as a transmission electron microscope (TEM) or a field emission scanning electron microscope (FE-SEM). In the case of a negative electrode active material containing the silicon particles, the sample can be cut with a focused ion beam (FIB) and the cross section can be observed with a FE-SEM, or the sample can be sliced and the state of the silicon particles can be identified by TEM observation. The aspect ratio of the silicon particles is a calculation result based on 50 particles in the main part of the sample within the field of view of the TEM image.
[0022] The active material containing the silicon particles of the present invention (hereinafter also referred to as the "silicon-containing active material of the present invention") is suitable for use as an active material for secondary batteries because it is not easily broken down even when lithium is inserted or released. The silicon-containing active material of the present invention may be the silicon particles themselves, or may be an active material containing the silicon particles of the present invention and a matrix phase described below.
[0023] When silicon particles are used as an active material, it is believed that the cycle performance is improved by the silicon in the active material being oriented in the (111) plane as described above. As described above, the silicon particles have a high degree of orientation to the (111) plane, with F(111) of 0.2 or more, and the (111) plane is well developed, so it is believed that the orientation of the silicon crystals in the silicon-containing active material in the (111) plane is maintained. From the above viewpoint, the degree of orientation of silicon in the silicon-containing active material, F(111), is preferably 0.03 or more, and more preferably 0.05 or more. The degree of orientation of silicon in the silicon-containing active material, F(111), is the degree of orientation of the (111) plane of silicon in the silicon-containing active material obtained from XRD by the 2θ-θ method and the Lotgering method, as described above, and is obtained from the above formulas (1) and (2).
[0024] The BET specific surface area of this silicon-containing active material is 50m from the viewpoint of electrical capacity and initial Coulombic efficiency. 2 / g or less is preferable, and 1.0m 2 / g or more 50m 2 / g or less is more preferable. When the BET specific surface area is within the above range, the amount of solvent absorbed during electrode preparation can be appropriately maintained, and the amount of binder used to maintain binding properties can also be appropriately maintained. The BET specific surface area is a value determined by the BET method as described above, and can be determined by nitrogen gas adsorption measurement, for example, using a specific surface area measurement device.
[0025] If the average particle size of the silicon-containing active material is too small, the specific surface area will increase significantly, and when the active material is used as the negative electrode active material in a secondary battery, the reversible charge / discharge capacity per unit volume may decrease due to an increase in the amount of solid-phase interface electrolyte decomposition products (hereinafter, also referred to as "SEI") generated during charging and discharging. If the average particle size is too large, there is a risk of the material peeling off from the current collector during electrode film production. Therefore, the volume average particle diameter of the present silicon-containing active material is preferably 2 μm or more and 20 μm or less. The volume average particle diameter of the present silicon-containing active material is more preferably 2.5 μm or more, and particularly preferably 3.0 μm or more. The volume average particle diameter of the present silicon-containing active material is more preferably 15 μm or less, even more preferably 12 μm or less, and particularly preferably 10 μm or less. The volume average particle diameter is the value of D50.
[0026] In the XRD of the silicon-containing active material, the crystallite diameter of the silicon particles in the silicon-containing active material that is assigned to the (111) plane is preferably 40 nm or less from the viewpoint of the initial coulombic efficiency and the capacity retention rate. The crystallite diameter is more preferably 35 nm or less, and further preferably 30 nm or less. The crystallite size is a value determined by the above-mentioned Scherrer method.
[0027] From the viewpoint of the stability of the active material for secondary batteries, it is preferable to use the present silicon-containing active material (hereinafter also referred to as the present silicon-containing composite active material) in which the matrix phase contains the present silicon particles as the active material for secondary batteries. When the silicon-containing composite active material is used as an active material for a secondary battery, the matrix phase is a material capable of absorbing and releasing lithium ions. The material capable of absorbing and releasing lithium ions is a material that can absorb lithium ions into the matrix phase during charging of the battery and release lithium ions from the matrix phase during discharging. The absorption and release cycle is repeated in the lithium secondary battery. Examples of materials capable of absorbing and releasing lithium ions include graphite, silicon dioxide, titanium oxide, and compounds containing silicon, oxygen, and carbon, and the matrix phase is preferably composed of these materials. Among these materials, from the viewpoint of improving the initial efficiency and capacity maintenance rate, a matrix phase composed of a compound containing at least one of silicon and carbon, such as graphite, silicon dioxide, a compound containing silicon, oxygen, and carbon, is preferred, and a matrix phase composed of a compound containing silicon, oxygen, and carbon is more preferred. Compounds containing silicon, oxygen, and carbon include silicon oxycarbide.
[0028] Silicon oxycarbide is composed of compounds containing silicon, oxygen, and carbon, and among these, a structure containing a three-dimensional network structure of a silicon-oxygen-carbon skeleton and free carbon is preferred. Here, free carbon is carbon that is not contained in the three-dimensional skeleton of silicon-oxygen-carbon. Free carbon includes carbon that exists as a carbon phase, carbon that is bonded to carbon in the carbon phase, and carbon that is bonded to the silicon-oxygen-carbon skeleton and the carbon phase.
[0029] The silicon oxycarbide is preferably represented by the following formula (4): SiOxCy (4) In formula (4), x represents the molar ratio of oxygen to silicon, and y represents the molar ratio of carbon to silicon. When the present silicon-containing composite active material is used in a secondary battery, from the viewpoint of obtaining an advantageous balance between charge / discharge performance and capacity retention rate, 1≦x<2 is preferable, 1≦x≦1.9 is more preferable, and 1≦x≦1.8 is even more preferable. Furthermore, when the silicon particle-containing composite active material is used in a secondary battery, from the viewpoint of the balance between charge / discharge performance and initial coulombic efficiency, 1≦y≦20 is preferable, and 1.2≦y≦15 is more preferable.
[0030] The above x and y can be obtained by measuring the mass content of each element and then converting it into a molar ratio (atomic number ratio). In this case, the oxygen and carbon contents can be quantified using an inorganic elemental analyzer, and the silicon content can be quantified using an inductively coupled plasma optical emission spectrometer (ICP-OES). It is preferable to measure x and y by the above-described method, but it is also possible to perform local analysis of the active material, obtain many measurement points of the content ratio data obtained thereby, and infer the content ratio of the entire active material. Examples of local analysis include energy dispersive X-ray spectroscopy (SEM-EDX) and electron probe microanalyzer (EPMA).
[0031] When the matrix phase is a silicon oxycarbide phase made of silicon oxycarbide and has a structure containing a three-dimensional network structure of a silicon-oxygen-carbon skeleton and free carbon, the silicon-oxygen-carbon skeleton in the silicon oxycarbide phase has high chemical stability, has a composite structure with free carbon, and exhibits small volume change with respect to the absorption and release of lithium. The silicon particles are tightly wrapped in a composite structure of a silicon-oxygen-carbon skeleton and free carbon, so that the volume change of the silicon particles with respect to the absorption and release of lithium is further suppressed. As a result, when the silicon particle-containing composite active material is used as a negative electrode active material, the silicon particles in the negative electrode play a role as a main component for expressing charge and discharge performance, while the silicon oxycarbide phase further suppresses the destruction of the particles associated with the volume change of the silicon particles during charge and discharge, and the cycle performance of the lithium secondary battery is further improved.
[0032] In addition, when the compound constituting the silicon oxycarbide phase has a three-dimensional network structure of a silicon-oxygen-carbon skeleton and a structure containing free carbon, the silicon-oxygen-carbon skeleton causes a change in the internal electron distribution of the silicon-oxygen-carbon skeleton due to the approach of lithium ions, and an electrostatic bond or a coordination bond is formed between the silicon-oxygen-carbon skeleton and the lithium ions. Lithium ions are stored in the silicon-oxygen-carbon skeleton by this electrostatic bond or coordination bond. On the other hand, since the coordination bond energy is relatively low, the desorption reaction of lithium ions is easily carried out. That is, it is considered that the silicon-oxygen-carbon skeleton can reversibly cause the insertion and desorption reactions of lithium ions during charge and discharge.
[0033] The silicon oxycarbide may contain nitrogen in addition to silicon, oxygen, and carbon. In the method for producing the composite active material containing silicon particles described later, nitrogen atoms contained in raw materials used, such as phenolic resins or polysiloxane compounds, other nitrogen compounds such as dispersants, and nitrogen gas used in the firing process, are used as atomic groups containing functional groups in the molecule, and the nitrogen atoms can be introduced into the silicon oxycarbide phase. When the silicon oxycarbide phase contains nitrogen, the charge-discharge performance and capacity retention rate tend to be excellent when the composite active material containing silicon particles is used as the negative electrode active material. When the compound constituting the silicon oxycarbide phase is a compound containing silicon, oxygen, carbon, and nitrogen, the silicon oxycarbide phase preferably contains a compound represented by the following formula (5). SiOaCbNc (5) In formula (5), a represents the molar ratio of oxygen to silicon, b represents the molar ratio of carbon to silicon, and c represents the molar ratio of nitrogen to silicon. When the silicon oxycarbide phase contains the compound represented by the formula (5), from the viewpoints of charge-discharge performance and capacity retention rate when the active material containing the silicon particles is used in a secondary battery, 1 ≦ a ≦ 2, 1 ≦ b ≦ 20, 0 < c ≦ 0.5 is preferable, and 1 ≦ a ≦ 1.9, 1.2 ≦ b ≦ 15, 0 < c ≦ 0.4 is more preferable.
[0034] The above-mentioned a, b and c can be determined by measuring the mass contents of the elements and then converting them into molar ratios (ratio of atomic numbers), similarly to the above-mentioned x and y. As with x and y, a, b and c are preferably measured by the above-described method, but it is also possible to perform local analysis of the silicon-containing active material, obtain many measurement points of the content ratio data obtained thereby, and infer the content ratio of the entire silicon-containing active material. Examples of local analysis include energy dispersive X-ray spectroscopy (SEM-EDX) and electron probe microanalyzer (EPMA).
[0035] In the case of an active material in which the matrix phase contains silicon oxycarbide, it is preferable that the silicon oxycarbide has a silicon-oxygen-carbon skeletal structure and free carbon composed only of carbon elements. When the silicon oxycarbide has free carbon, the active material has a Raman spectrum of 1590 cm 2 assigned to the G band of the graphite long-period carbon lattice structure. -1 and 1330 cm, which is assigned to the D band of the disordered and defective graphitic short-period carbon lattice structure. -1 A scattering peak around the scattering peak intensity is observed. The intensity ratio of the scattering peak intensity of the D band, I(D band), to the scattering peak intensity of the D band, I(G band), I(G band) / I(D band), is preferably 0.7 or more and 2 or less. The scattering peak intensity ratio, I(G band) / I(D band), is more preferably 0.7 or more and 1.8 or less. The fact that the scattering peak intensity ratio, I(G band) / I(D band), is in the above range means that the following can be said about the free carbon in the matrix.
[0036] Some carbon atoms of the free carbon are bonded to some silicon atoms in the silicon-oxygen-carbon skeleton. This free carbon is an important component that affects the charge-discharge characteristics. The free carbon is mainly formed in the silicon-oxygen-carbon skeleton composed of SiO2C2, SiO3C, and SiO4, and is bonded to some silicon atoms in the silicon-oxygen-carbon skeleton, so that electron transfer between the silicon atoms inside the silicon-oxygen-carbon skeleton and on the surface and the free carbon becomes easier. Therefore, when an active material in which the matrix phase contains the present silicon particles is used as a negative electrode active material in a secondary battery, the insertion and desorption reaction of lithium ions during charging and discharging proceeds quickly, and the charge-discharge characteristics are improved. In addition, the insertion and desorption reaction of lithium ions may cause the active material to expand and contract, but the presence of free carbon in its vicinity is thought to have the effect of mitigating the expansion and contraction of the entire active material, thereby greatly improving the capacity retention rate.
[0037] The free carbon is formed by pyrolysis of the silicon-containing compound and the carbon source resin in an inert gas atmosphere during the production of the silicon oxycarbide phase. Specifically, carbonizable sites in the molecular structures of the silicon-containing compound and the carbon source resin are converted into carbon components by high-temperature pyrolysis in an inactive atmosphere, and some of these carbons are bonded to a part of the silicon-oxygen-carbon skeleton. The carbonizable components are preferably hydrocarbons, more preferably alkyls, alkylenes, alkenes, alkynes, and aromatics, and even more preferably aromatics.
[0038] In addition, the presence of free carbon is expected to reduce the resistance of the active material, and when the active material is used as the negative electrode of a secondary battery, the reaction inside the active material occurs uniformly and smoothly, and it is believed that a secondary battery active material with an excellent balance between charge / discharge performance and capacity retention rate can be obtained. Although the introduction of free carbon is possible only from silicon-containing compounds, the use of a carbon source resin in combination is expected to increase the amount of free carbon present and its effect. The type of carbon source resin is not particularly limited, but a carbon compound containing a six-membered carbon ring is preferred.
[0039] The state of the free carbon can be identified by a thermogravimetric differential thermal analyzer (TG-DTA) in addition to Raman spectroscopy. Unlike the carbon atoms in a silicon-oxygen-carbon skeleton, free carbon is easily thermally decomposed in the atmosphere, and the amount of carbon present can be determined from the amount of thermal weight loss measured in the presence of air. In other words, the amount of carbon can be quantified using TG-DTA. In addition, from the thermal weight loss behavior, the changes in the thermal decomposition temperature behavior, such as the decomposition reaction start temperature, the decomposition reaction end temperature, the number of thermal decomposition reaction species, and the temperature of the maximum weight loss amount in each thermal decomposition reaction species, can be easily understood. The state of carbon can be determined using the temperature values of these behaviors. On the other hand, the carbon atoms in the silicon-oxygen-carbon skeleton, that is, the carbon atoms bonded to the silicon atoms constituting the SiO2C2, SiO3C, and SiO4, have a very strong chemical bond and are therefore highly thermally stable, and are not considered to be thermally decomposed in the air within the temperature range of the thermal analysis device measurement. In addition, the carbon in the silicon oxycarbide phase of the active material has properties similar to those of amorphous carbon, so it is thermally decomposed in the air in the temperature range of about 550°C to 900°C. As a result, a rapid weight loss occurs. The maximum temperature of the measurement conditions for TG-DTA is not particularly limited, but in order to completely terminate the thermal decomposition reaction of carbon, it is preferable to perform the TG-DTA measurement in the air under conditions of about 25°C to about 1000°C or higher.
[0040] The surface of the silicon-containing active material may be coated with a coating material, preferably a material that is expected to have electron conductivity, lithium ion conductivity, and the effect of inhibiting decomposition of the electrolyte. The coating material includes electron conductive materials such as carbon, titanium, nickel, etc. Among these, from the viewpoint of improving the chemical stability and thermal stability of the active material, carbon is preferred, and low crystalline carbon is more preferred.
[0041] When the coating material is low-crystalline carbon, the average thickness of the coating layer is preferably 10 nm to 300 nm, and the content of low-crystalline carbon is preferably 1 to 30 mass % relative to the total amount of the silicon-containing active material, which is 100 mass %. When the coating material is carbon, the carbon coating is preferably formed on the surface of the active material by a vapor deposition method. The amount of the carbon coating is preferably 1% by mass or more and 10% by mass or less, where the total amount of the mass of the silicon-containing active material and the mass of the carbon coating is 100% by mass, from the viewpoint of improving the chemical stability and thermal stability of the active material. The mass of the silicon-containing active material is the mass of the silicon particles when the silicon-containing active material is composed only of the silicon particles, and is the total amount of the silicon particles and the matrix phase when the active material is composed of the silicon particles. For example, when the matrix phase is silicon oxycarbide, it is the total amount of the silicon particles and the silicon oxycarbide. When the silicon oxycarbide contains nitrogen, it is the total amount including the nitrogen. When the silicon-containing active material contains another third component described later, it is the total amount including the third component.
[0042] The silicon particles are produced by pulverizing silicon chunks or the like into particles, and during production, the silicon particles are pulverized so that the (111) planes of the silicon particles grow to form particles with shape anisotropy. As a method for crushing silicon particles so that the (111) plane of the silicon particles grows into particles having shape anisotropy, for example, a method for crushing the silicon particles so that the particle size of the silicon particles is not made too small and the silicon particles exfoliate on the (111) plane can be mentioned. Examples of the pulverizer used for pulverizing the silicon chunks and the like to produce silicon particles include pulverizers such as a ball mill, a bead mill, a jet mill, etc. The pulverization may be wet pulverization using an organic solvent, and examples of the organic solvent include aromatic hydrocarbon solvents such as alcohols, ketones, toluene, xylene, naphthalene, and methylnaphthalene. In this case, by controlling conditions such as the ball particle size, bead particle size, ejection pressure, grinder rotation speed, or grinding time so that the particle size does not become too small and the grinding energy is reduced, particles with a relatively small particle size can be obtained. After the particle size is reduced to a certain degree, further crushing is performed with a weak force so that the silicon particles are crushed to peel off from the (111) plane, thereby making it possible to obtain particles having shape anisotropy. From the viewpoint of being able to control the shape anisotropy of the silicon particles, a crushing method using a bead mill in which the particle size of the beads and the crushing time are controlled to crush the silicon particles is preferred.
[0043] For example, silicon chunks or the like can be pulverized using a grinder to a particle size of about 100 nm to 500 nm, and then, using a bead mill using beads with a diameter of, for example, 0.05 mm, the silicon particles can be made into particles with shape anisotropy in which the (111) has grown. When the present silicon particles are produced by a bead mill, the method of grinding can be exemplified by a method of successively decreasing the average particle diameter of beads from large to small in multiple steps. It is also preferable to make the grinding time longer with the average particle diameter of small beads than with the average particle diameter of large beads. For example, the method of grinding large-diameter silicon particles with an average particle diameter of about 100 nm to 500 nm obtained by grinding silicon chunks using beads with an average particle diameter of 0.2 mm or more for, for example, 1 hour or more, and then grinding for a long time, for example, 5 hours or more, using beads with an average particle diameter of 0.05 mm to 0.1 mm.
[0044] If the purity of the silicon chunks used is less than 99% by mass, the metal may easily dissolve when the silicon particles are used as a negative electrode active material, making it difficult to handle the battery. Therefore, the purity of the silicon particles used is preferably 99% by mass or more, more preferably 99.9% by mass, and even more preferably 99.99% by mass.
[0045] The pulverization is usually carried out in an inert gas atmosphere, preferably a nitrogen atmosphere from the viewpoint of handling, and is preferably a wet pulverization in which silicon chunks or the like are pulverized in a non-aqueous solvent. Examples of non-aqueous solvents include ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and diisobutyl ketone; alcohols such as ethanol, methanol, normal propyl alcohol, and isopropyl alcohol; and aromatics such as benzene, toluene, and xylene. The concentration of the silicon chunks or the like in the non-aqueous solvent is about 5 to 50 mass %.
[0046] In the wet grinding, a dispersant may be added to promote grinding of silicon chunks, etc. The type of dispersant may be an aqueous or non-aqueous dispersant, and a non-aqueous dispersant is preferred. The type of non-aqueous dispersant may be a polymer type such as a polyether type, an alcohol type, a polyalkylene polyamine type, or a polycarboxylic acid partial alkyl ester type, a low molecular type such as a polyhydric alcohol ester type or an alkyl polyamine type, or an inorganic type such as a polyphosphate type. When the dispersant is added, the amount is preferably in the range of 5% by mass to 60% by mass, and more preferably 5% by mass to 40% by mass, based on the mass of the silicon chunks or the like.
[0047] Furthermore, in the wet grinding, at least one surfactant selected from the group consisting of cationic surfactants, anionic surfactants, and amphoteric surfactants may be added to improve the dispersibility of silicon lumps and the like and promote the grinding of silicon lumps and the like. Examples of cationic surfactants include aliphatic amine salts, aliphatic quaternary ammonium salts, aromatic quaternary ammonium salts, and heterocyclic quaternary ammonium salts. The amine value of the cationic surfactant is, for example, 1 to 100 mgKOH / g, preferably 5 to 80 mgKOH / g, more preferably 10 to 48 mgKOH / g, and particularly preferably 35 to 48 mgKOH / g. When the amine value is within the above range, re-aggregation of silicon particles nano-sized by pulverization can be suppressed, and the viscosity of the slurry can be suppressed, resulting in excellent cycle characteristics, charge / discharge capacity, and initial coulombic efficiency in the battery. Specifically, DISPERBYK9077 (manufactured by BYK Additives&Instruments, DISPERBYK is a registered trademark) can be used as the cationic surfactant.
[0048] Examples of the anionic surfactant include carboxylates, sulfonates, sulfates, and phosphates. The acid value of the anionic surfactant is, for example, 1 to 200 mgKOH / g, preferably 10 to 180 mgKOH / g, and more preferably 50 to 150 mgKOH / g. When the acid value is within the above range, the wettability of the silicon particles to the dispersion medium is improved, so that the viscosity of the slurry can be suppressed, and as a result, the cycle characteristics, charge / discharge capacity, and initial coulombic efficiency of the battery are excellent. Specifically, DISPERBYK111 (manufactured by BYK Additives&Instruments) can be used as the anionic surfactant.
[0049] The surfactant may be an amphoteric surfactant having the above amine value and acid value, or a cationic surfactant and an anionic surfactant having the above amine value and acid value may be used in combination. The amphoteric surfactant is a surfactant that exhibits the properties of an anionic surfactant in the alkaline range and the properties of a cationic surfactant in the acidic range, and examples of such surfactants include compounds containing carboxylates, amino acids, and betaines. Specifically, ANTI-TERRA (registered trademark)-U100 (manufactured by BYK Additives & Instruments) can be used as the amphoteric surfactant. When the surfactant is added, the amount added is preferably 5 to 60 mass %, more preferably 5 to 40 mass %, and further preferably 5 to 20 mass %, based on the mass of the silicon particles.
[0050] When the present silicon-containing composite active material is used, the present silicon-containing composite active material can be produced, for example, by mixing the present silicon particles with a resin, drying the mixture, and then firing it in an inert gas atmosphere. As described above, the matrix phase is composed of a material capable of absorbing and releasing lithium ions, so the resin to be mixed with the silicon particles may be any resin that can become a material capable of absorbing and releasing lithium ions by baking. As described above, examples of materials capable of absorbing and releasing lithium ions include graphite, silicon dioxide, titanium oxide, and compounds containing silicon, oxygen, and carbon, so examples of resins to be mixed with the silicon particles include polysiloxane resins and carbon source resins.
[0051] When the present silicon particles are mixed with a resin, from the viewpoint of uniformly mixing the two, it is preferable to use the present silicon particles as a silicon particle slurry in which the present silicon particles are dispersed in a solvent. From the viewpoint of dispersibility, the silicon particle slurry is preferably a silicon particle slurry containing the present silicon particles, a dispersant and a solvent. The dispersant contained in the silicon particle slurry is the same as above, and the solvent is water or the same non-aqueous solvent as the non-aqueous solvent. The preferred dispersant and non-aqueous solvent are also the same as above. The silicon particle slurry may also contain a surfactant. The surfactant may be at least one selected from the group consisting of the cationic surfactant, the anionic surfactant, and the amphoteric surfactant as above. The silicon particle slurry preferably contains the silicon particles, a dispersant and a non-aqueous solvent.
[0052] When the matrix phase of the silicon-containing composite active material contains silicon oxycarbide, it is preferable to use a mixture of a polysiloxane compound and a carbon source resin as the resin.When the mixture of a polysiloxane compound and a carbon source resin is mixed with the silicon particles, it is preferable to use the silicon particle slurry. The slurry containing the present silicon particles is mixed with a mixture of a polysiloxane compound and a carbon source resin, the solvent is removed to obtain a precursor, the obtained precursor is fired to obtain a fired product, and the fired product is pulverized as necessary to obtain the desired present silicon-containing composite active material.
[0053] The polysiloxane compound may be a resin containing at least one of a polycarbosilane structure, a polysilazane structure, a polysilane structure, and a polysiloxane structure. The resin may be a resin containing only these structures, or a composite resin having at least one of these structures as a segment and chemically bonded to other polymer segments. The form of the composite may be graft copolymerization, block copolymerization, random copolymerization, alternating copolymerization, etc. For example, a composite resin having a graft structure in which a polysiloxane segment is chemically bonded to the side chain of a polymer segment, a composite resin having a block structure in which a polysiloxane segment is chemically bonded to the end of a polymer segment, etc. may be mentioned.
[0054] The polysiloxane segment is preferably a polysiloxane compound having a structural unit represented by the following general formula (S-1) and / or the following general formula (S-2): In particular, the polysiloxane compound more preferably has a carboxy group, an epoxy group, an amino group, or a polyether group on the side chain or terminal of the siloxane bond (Si-O-Si) main skeleton.
[0055] [ka]
[0056] [ka] In the general formulas (S-1) and (S-2), R 1 R represents an aromatic hydrocarbon group, an alkyl group, an epoxy group, a carboxy group, or the like, which may have a substituent. 2 and R 3 respectively represent an alkyl group, a cycloalkyl group, an aryl group, an aralkyl group, an epoxy group, a carboxy group, or the like.
[0057] Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a 1-methylbutyl group, a 2-methylbutyl group, a 1,2-dimethylpropyl group, a 1-ethylpropyl group, a hexyl group, an isohexyl group, a 1-methylpentyl group, a 2-methylpentyl group, a 3-methylpentyl group, a 1,1-dimethylbutyl group, a 1,2-dimethylbutyl group, a 2,2-dimethylbutyl group, a 1-ethylbutyl group, a 1,1,2-trimethylpropyl group, a 1,2,2-trimethylpropyl group, a 1-ethyl-2-methylpropyl group, a 1-ethyl-1-methylpropyl group, etc. Examples of the cycloalkyl group include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, etc.
[0058] Examples of the aryl group include a phenyl group, a naphthyl group, a 2-methylphenyl group, a 3-methylphenyl group, a 4-methylphenyl group, a 4-vinylphenyl group, and a 3-isopropylphenyl group.
[0059] Examples of the aralkyl group include a benzyl group, a diphenylmethyl group, and a naphthylmethyl group.
[0060] Examples of polymer segments other than the polysiloxane segment contained in the polysiloxane compound include vinyl polymer segments such as acrylic polymers, fluoroolefin polymers, vinyl ester polymers, aromatic vinyl polymers, and polyolefin polymers, as well as polymer segments such as polyurethane polymer segments, polyester polymer segments, and polyether polymer segments. Among these, vinyl polymer segments are preferred.
[0061] The polysiloxane compound may be a composite resin in which a polysiloxane segment and a polymer segment are bonded in a structure represented by the following structural formula (S-3), or may have a three-dimensional network polysiloxane structure.
[0062] [ka] In the formula, the carbon atom is a carbon atom that constitutes a polymer segment, and the two silicon atoms are silicon atoms that constitute a polysiloxane segment.
[0063] The polysiloxane segment of the polysiloxane compound may have a functional group capable of reacting by heating, such as a polymerizable double bond, in the polysiloxane segment. By subjecting the polysiloxane compound to heat treatment before thermal decomposition, a crosslinking reaction progresses and the compound is solidified, which makes it easy to carry out the thermal decomposition treatment.
[0064] Examples of the polymerizable double bond include a vinyl group and a (meth)acryloyl group. The number of polymerizable double bonds in the polysiloxane segment is preferably 2 or more, more preferably 3 to 200, and even more preferably 3 to 50. In addition, by using a composite resin having 2 or more polymerizable double bonds as the polysiloxane compound, the crosslinking reaction can be easily promoted.
[0065] The polysiloxane segment may have a silanol group and / or a hydrolyzable silyl group. Examples of the hydrolyzable group in the hydrolyzable silyl group include a halogen atom, an alkoxy group, a substituted alkoxy group, an acyloxy group, a phenoxy group, a mercapto group, an amino group, an amide group, an aminooxy group, an iminoxy group, and an alkenyloxy group. The hydrolyzable silyl group becomes a silanol group by hydrolysis of these groups. In parallel with the thermosetting reaction, a hydrolysis condensation reaction proceeds between the hydroxyl group in the silanol group and the hydrolyzable group in the hydrolyzable silyl group, thereby obtaining a solid polysiloxane compound.
[0066] The silanol group in the present invention is a silicon-containing group having a hydroxyl group directly bonded to a silicon atom. The hydrolyzable silyl group in the present invention is a silicon-containing group having a hydrolyzable group directly bonded to a silicon atom, and specifically includes, for example, a group represented by the following general formula (S-4).
[0067] [ka] In the formula, R 4 R represents a monovalent organic group such as an alkyl group, an aryl group, or an aralkyl group. 5 is a halogen atom, an alkoxy group, an acyloxy group, an allyloxy group, a mercapto group, an amino group, an amido group, an aminooxy group, an iminoxy group or an alkenyloxy group, and b is an integer of 0 to 2.
[0068] Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a 1-methylbutyl group, a 2-methylbutyl group, a 1,2-dimethylpropyl group, a 1-ethylpropyl group, a hexyl group, an isohexyl group, a 1-methylpentyl group, a 2-methylpentyl group, a 3-methylpentyl group, a 1,1-dimethylbutyl group, a 1,2-dimethylbutyl group, a 2,2-dimethylbutyl group, a 1-ethylbutyl group, a 1,1,2-trimethylpropyl group, a 1,2,2-trimethylpropyl group, a 1-ethyl-2-methylpropyl group, and a 1-ethyl-1-methylpropyl group.
[0069] Examples of the aryl group include a phenyl group, a naphthyl group, a 2-methylphenyl group, a 3-methylphenyl group, a 4-methylphenyl group, a 4-vinylphenyl group, and a 3-isopropylphenyl group.
[0070] Examples of the aralkyl group include a benzyl group, a diphenylmethyl group, and a naphthylmethyl group.
[0071] Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.
[0072] Examples of the alkoxy group include a methoxy group, an ethoxy group, a propoxy group, an isopropoxy group, a butoxy group, a sec-butoxy group, and a tert-butoxy group.
[0073] Examples of the acyloxy group include a formyloxy group, an acetoxy group, a propanoyloxy group, a butanoyloxy group, a pivaloyloxy group, a pentanoyloxy group, a phenylacetoxy group, an acetoacetoxy group, a benzoyloxy group, and a naphthoyloxy group.
[0074] Examples of the allyloxy group include a phenyloxy group and a naphthyloxy group.
[0075] Examples of the alkenyloxy group include a vinyloxy group, an allyloxy group, a 1-propenyloxy group, an isopropenyloxy group, a 2-butenyloxy group, a 3-butenyloxy group, a 2-pentenyloxy group, a 3-methyl-3-butenyloxy group, and a 2-hexenyloxy group.
[0076] Examples of the polysiloxane segment having the structural unit represented by the general formula (S-1) and / or the general formula (S-2) include those having the following structures.
[0077] [ka]
[0078] [ka]
[0079] [ka]
[0080] The polymer segment may have various functional groups as necessary within the scope of not impairing the effects of the present invention. Examples of such functional groups include a carboxyl group, a blocked carboxyl group, a carboxylic anhydride group, a tertiary amino group, a hydroxyl group, a blocked hydroxyl group, a cyclocarbonate group, an epoxy group, a carbonyl group, a primary amide group, a secondary amide group, a carbamate group, and a functional group represented by the following structural formula (S-5).
[0081] [ka]
[0082] The polymer segment may also have a polymerizable double bond such as a vinyl group or a (meth)acryloyl group.
[0083] The polysiloxane compound is preferably produced, for example, by the following methods (i) to (iii).
[0084] (i) A method in which a polymer segment containing a silanol group and / or a hydrolyzable silyl group is prepared in advance as a raw material for the polymer segment, and this polymer segment is mixed with a silane compound having both a silanol group and / or a hydrolyzable silyl group and a polymerizable double bond, and a hydrolysis condensation reaction is carried out.
[0085] (ii) A method in which a polymer segment containing a silanol group and / or a hydrolyzable silyl group is prepared in advance as a raw material for the polymer segment. A polysiloxane is also prepared in advance by subjecting a silane compound having both a silanol group and / or a hydrolyzable silyl group and a polymerizable double bond to a hydrolysis and condensation reaction. The polymer segment and the polysiloxane are then mixed together to carry out a hydrolysis and condensation reaction.
[0086] (iii) A method in which the polymer segment, a silane compound having a silanol group and / or a hydrolyzable silyl group, and a polymerizable double bond, and a polysiloxane are mixed together, and a hydrolysis condensation reaction is carried out. A polysiloxane compound can be obtained by the above method. Examples of polysiloxane compounds include the Ceranate (registered trademark) series (organic / inorganic hybrid coating resin; manufactured by DIC Corporation) and the Compocelan SQ series (silsesquioxane hybrid; manufactured by Arakawa Chemical Industries, Ltd.).
[0087] The carbon source resin is preferably a synthetic resin or natural chemical raw material that has good miscibility with polysiloxane compounds, is carbonized by high-temperature baking in an inert atmosphere, and has an aromatic functional group.
[0088] Examples of synthetic resins include thermoplastic resins such as polyvinyl alcohol and polyacrylic acid, and thermosetting resins such as phenol resins and furan resins. Examples of natural chemical raw materials include heavy oils, particularly tar pitches, such as coal tar, light tar oil, medium tar oil, heavy tar oil, naphthalene oil, anthracene oil, coal tar pitch, pitch oil, mesophase pitch, oxygen-crosslinked petroleum pitch, and heavy oil. From the viewpoints of cheap availability and removal of impurities, the use of phenol resins is more preferable.
[0089] In particular, the carbon source resin is preferably a resin containing an aromatic hydrocarbon moiety, and the resin containing an aromatic hydrocarbon moiety is preferably a phenol resin, an epoxy resin, or a thermosetting resin, and the phenol resin is preferably a resol type. Examples of phenolic resins include SUMILITE resin series (resole type phenolic resins, manufactured by Sumitomo Bakelite Co., Ltd.).
[0090] The slurry containing the silicon particles is mixed with the mixture of the polysiloxane compound and the carbon source resin, and the solvent is removed to obtain a precursor. The mixture containing the polysiloxane compound and the carbon source resin is preferably in a state in which the polysiloxane compound and the carbon source resin are uniformly mixed. The mixing is performed using a device having the functions of dispersion and mixing. Examples of the device having the functions of dispersion and mixing include a stirrer, an ultrasonic mixer, and a premix disperser. In the work of desolvation and drying for the purpose of distilling off the organic solvent, a dryer, a reduced pressure dryer, a spray dryer, etc. can be used.
[0091] The precursor preferably contains 3% to 50% by mass of the present silicon particles, 15% to 85% by mass of a solid content of the polysiloxane compound, and 3% to 70% by mass of a solid content of the carbon source resin, and more preferably contains 8% to 40% by mass of the present silicon oxide particles, 20 to 70% by mass of a solid content of the polysiloxane compound, and 3% to 60% by mass of a solid content of the carbon source resin.
[0092] The precursor obtained above is calcined in an inert gas atmosphere to completely decompose the thermally decomposable organic components, thereby obtaining a calcined product. The calcination temperature is, for example, a maximum temperature in the range of 900°C to 1200°C, which allows the thermally decomposable organic components to be completely decomposed. The polysiloxane compound and the carbon source resin are converted by the energy of the high-temperature treatment into a silicon oxycarbide phase having a silicon-oxygen-carbon skeleton and free carbon.
[0093] The firing is carried out according to a firing program that is determined by the heating rate, holding time at a constant temperature, etc. The maximum temperature is the highest temperature that can be set, and it strongly influences the structure and performance of the fired product. The maximum temperature can precisely control the microstructure of the silicon-containing active material that retains the chemical bond state of silicon and carbon in the silicon oxycarbide phase, resulting in better charge / discharge characteristics.
[0094] The calcination method is not particularly limited, but a reaction device having a heating function in an inert gas atmosphere may be used, and treatment may be performed by a continuous method or a batch method. The calcination device may be appropriately selected from a fluidized bed reactor, a rotary furnace, a vertical moving bed reactor, a tunnel furnace, a batch furnace, a rotary kiln, etc. according to the purpose.
[0095] The obtained fired product is pulverized and classified as necessary to obtain the silicon particle-containing composite active material. The pulverization may be performed in one step to the desired particle size, or may be performed in several steps. For example, when preparing an active material of about 10 μm, the fired product of lumps or aggregates of 10 mm or more is coarsely pulverized with a jaw crusher, roll crusher, etc. to particles of about 1 mm, then crushed to about 100 μm with a glow mill, ball mill, etc., and crushed to about 10 μm with a bead mill, jet mill, etc. The particles produced by pulverization may contain coarse particles, and classification is performed to remove them, or to remove fine powder and adjust the particle size distribution. The classifier used is a wind classifier, a wet classifier, etc., depending on the purpose, but when removing coarse particles, a classification method that passes through a sieve is preferable because it can reliably achieve the purpose. In addition, if the precursor mixture is controlled to a shape near the target particle size by spray drying or the like before firing, and fired in that shape, it is possible to omit the pulverization process.
[0096] When the silicon particle-containing composite active material of the present invention has a silicate compound of at least one metal selected from the group consisting of Li, K, Na, Ca, Mg, and Al, a salt of at least one metal selected from the group consisting of Li, K, Na, Ca, Mg, and Al is added to a suspension obtained by mixing a slurry of the silicon particles of the present invention with a mixture of a polysiloxane compound and a carbon source resin, and then the same operation as above is performed to obtain the silicon-containing active material of the present invention having the silicate compound. Examples of the salt of at least one metal selected from the group consisting of Li, K, Na, Ca, Mg, and Al include halides such as fluorides, chlorides, and bromides, hydroxides, and carbonates of these metals.
[0097] The salt of the metal may be a salt of two or more metals, one salt may have a plurality of metals, or it may be a mixture of salts having different metals. The amount of the metal salt added to the suspension is preferably 0.01 to 0.4 in terms of molar ratio relative to the number of moles of silicon oxide particles. When the metal salt is soluble in an organic solvent, the metal salt may be dissolved in an organic solvent and added to the suspension and mixed. When the metal salt is insoluble in an organic solvent, the metal salt particles may be dispersed in an organic solvent and then added to the suspension and mixed. From the viewpoint of improving the dispersion effect, the metal salt is preferably nanoparticles having an average particle size of 100 nm or less. As the organic solvent, alcohols, ketones, etc. can be suitably used, but aromatic hydrocarbon solvents such as toluene, xylene, naphthalene, and methylnaphthalene can also be used.
[0098] The present silicon-containing active material has excellent cycle properties, and a secondary battery using the present silicon-containing active material as a negative electrode active material for a secondary battery exhibits excellent characteristics. Specifically, a slurry containing the silicon-containing active material, an organic binder, and other components such as a conductive assistant, if necessary, can be applied to a copper foil collector in the form of a thin film to form a negative electrode. Alternatively, a carbon material such as graphite can be added to the slurry to form a negative electrode. Examples of the carbon material include natural graphite, artificial graphite, and amorphous carbon such as hard carbon or soft carbon.
[0099] For example, the present silicon-containing active material and a binder, which is an organic binding material, are kneaded together with a solvent using a dispersing device such as a stirrer, a ball mill, a super sand mill, or a pressure kneader to prepare a negative electrode material slurry, which is then applied to a current collector to form a negative electrode layer. Alternatively, the negative electrode material can be obtained by forming the paste-like negative electrode material slurry into a sheet, pellet, or other shape and integrating it with a current collector.
[0100] Examples of the organic binder include styrene-butadiene rubber copolymers (hereinafter also referred to as "SBR"); ethylenically unsaturated carboxylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, (meth)acrylonitrile, and hydroxyethyl (meth)acrylate, and unsaturated carboxylic acid copolymers such as (meth)acrylic copolymers composed of ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, fumaric acid, and maleic acid; and polymer compounds such as polyvinylidene fluoride, polyethylene oxide, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polyimide, polyamideimide, and carboxymethylcellulose (hereinafter also referred to as "CMC").
[0101] Depending on their physical properties, these organic binders may be dispersed or dissolved in water, or dissolved in an organic solvent such as N-methyl-2-pyrrolidone (NMP), etc. The content of the organic binder in the negative electrode layer of the lithium ion secondary battery negative electrode is preferably 1 mass % to 30 mass %, more preferably 2 mass % to 20 mass %, and even more preferably 3 mass % to 15 mass %.
[0102] When the content of the organic binder is 1% by mass or more, the adhesion is better and the destruction of the negative electrode structure due to the expansion and contraction during charging and discharging is more suppressed, whereas when the content is 30% by mass or less, the increase in the electrode resistance is more suppressed. Within this range, the silicon-containing active material of the present invention has high chemical stability and can employ an aqueous binder, making it easy to handle in practical applications.
[0103] In addition, the negative electrode material slurry may be mixed with a conductive assistant as necessary. Examples of the conductive assistant include carbon black, graphite, acetylene black, and oxides and nitrides that exhibit conductivity. The amount of the conductive assistant used may be about 1% by mass to 15% by mass with respect to the negative electrode active material of the present invention.
[0104] The material and shape of the current collector may be, for example, a strip of copper, nickel, titanium, stainless steel, etc. in the form of foil, perforated foil, mesh, etc. Also, porous materials such as porous metal (foamed metal) and carbon paper can be used.
[0105] Examples of the method for applying the negative electrode material slurry to the current collector include metal mask printing, electrostatic coating, dip coating, spray coating, roll coating, doctor blade, gravure coating, screen printing, etc. After application, it is preferable to perform a rolling treatment using a flat plate press, a calendar roll, etc., as necessary.
[0106] The negative electrode material slurry may be formed into a sheet or pellet shape, and this may be integrated with the current collector by, for example, rolling, pressing, or a combination of these.
[0107] The negative electrode layer formed on the current collector or the negative electrode layer integrated with the current collector is preferably heat-treated according to the organic binder used. For example, when a water-based styrene-butadiene rubber copolymer (SBR) is used, the heat treatment may be performed at 100 to 130°C, and when an organic binder having a polyimide or polyamideimide as the main skeleton is used, the heat treatment is preferably performed at 150 to 450°C.
[0108] This heat treatment removes the solvent, hardens the binder, and increases the strength, improving the adhesion between the particles and between the particles and the current collector. It is preferable to carry out these heat treatments in an inert atmosphere such as helium, argon, or nitrogen, or in a vacuum atmosphere, in order to prevent oxidation of the current collector during the treatment.
[0109] In addition, it is preferable to subject the negative electrode to pressure treatment after the heat treatment. In the negative electrode using the present silicon-containing active material, the electrode density is 1 g / cm 3 from 1.8 g / cm 3 and preferably 1.1 g / cm 3 to 1.7 g / cm 3More preferably, it is 1.2 g / cm 3 from 1.6 g / cm 3 It is more preferable that the electrode density is higher. The higher the electrode density, the more the adhesion and the volumetric capacity density of the electrode tend to improve. On the other hand, if the electrode density is too high, the voids in the electrode are reduced, which weakens the effect of suppressing the volume expansion of silicon, etc., and the capacity retention rate may decrease. Therefore, the optimal range of the electrode density is selected.
[0110] The secondary battery of the present invention contains the silicon-containing active material in the negative electrode. As the secondary battery having a negative electrode containing the silicon-containing active material, non-aqueous electrolyte secondary batteries and solid electrolyte secondary batteries are preferable, and the silicon-containing active material exhibits excellent performance particularly when used as the negative electrode of a non-aqueous electrolyte secondary battery.
[0111] When the secondary battery of the present invention is used as a wet electrolyte secondary battery, for example, the secondary battery can be constructed by disposing a positive electrode and a negative electrode containing the present silicon particle-containing negative electrode active material opposite each other via a separator and injecting an electrolyte solution.
[0112] The positive electrode can be obtained by forming a positive electrode layer on the surface of a current collector in the same manner as the negative electrode. In this case, the current collector can be a strip of a metal or alloy such as aluminum, titanium, or stainless steel in the form of a foil, a perforated foil, a mesh, or the like.
[0113] There are no particular limitations on the positive electrode material used in the positive electrode layer. When preparing a lithium ion secondary battery among non-aqueous electrolyte secondary batteries, for example, a metal compound, metal oxide, metal sulfide, or conductive polymer material capable of doping or intercalating lithium ions may be used. For example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), and composite oxides thereof (LiCoxNiyMnzO2, x+y+z=1), lithium manganese spinel (LiMn2O4), lithium vanadium compounds, V2O5, V6O 13, VO2, MnO2, TiO2, MoV2O8, TiS2, V2S5, VS2, MoS2, MoS3, Cr3O8, Cr2O5, olivine-type LiMPO4 (wherein M is Co, Ni, Mn, or Fe), conductive polymers such as polyacetylene, polyaniline, polypyrrole, polythiophene, polyacene, porous carbon, etc. can be used alone or in combination.
[0114] As the separator, for example, a nonwoven fabric, cloth, microporous film, or a combination thereof, mainly composed of polyolefin such as polyethylene or polypropylene can be used. Note that if the positive electrode and the negative electrode of the nonaqueous electrolyte secondary battery to be produced are not in direct contact with each other, there is no need to use a separator.
[0115] As the electrolyte, for example, a so-called organic electrolyte can be used in which a lithium salt such as LiClO4, LiPF6, LiAsF6, LiBF4, or LiSO3CF3 is dissolved in a non-aqueous solvent such as ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, fluoroethylene carbonate, cyclopentanone, sulfolane, 3-methylsulfolane, 2,4-dimethylsulfolane, 3-methyl-1,3-oxazolidin-2-one, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, butyl methyl carbonate, ethyl propyl carbonate, butyl ethyl carbonate, dipropyl carbonate, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, methyl acetate, or ethyl acetate, or a mixture of two or more components.
[0116] The structure of the secondary battery of the present invention is not particularly limited, but usually, the positive electrode, the negative electrode, and a separator provided as necessary are wound into a flat spiral shape to form a wound electrode plate group, or these are stacked in a flat plate shape to form a stacked electrode plate group, and these electrode plate groups are generally sealed in an exterior body. Note that the half cell used in the examples of the present invention has a negative electrode mainly made of the present silicon-containing active material, and a simple evaluation was performed using metallic lithium as the counter electrode, in order to more clearly compare the cycleability of the active material itself.
[0117] The secondary battery using the silicon-containing active material is not particularly limited, but may be used as a paper-type battery, a button-type battery, a coin-type battery, a laminated battery, a cylindrical battery, a square battery, etc. The above-mentioned negative electrode active material of the present invention can also be applied to electrochemical devices in general that use the insertion and desorption of lithium ions as a charging and discharging mechanism, such as hybrid capacitors and solid lithium secondary batteries.
[0118] As described above, when the present silicon-containing active material is used as the negative electrode active material of a secondary battery, it gives a secondary battery with excellent cycle properties. The silicon-containing active material can be used as a negative electrode by the above-mentioned method to produce a secondary battery having the negative electrode.
[0119] The present silicon particles, the present silicon-containing active material and the present silicon particle-containing negative electrode active material containing the present silicon particles, and a secondary battery containing the present silicon particle-containing negative electrode active material in the negative electrode have been described above, but the present invention is not limited to the configurations of the above embodiments. The present silicon particles, the present silicon-containing active material containing the present silicon particles, the present silicon particle-containing negative electrode active material, and a secondary battery containing the present silicon particle-containing negative electrode active material in the negative electrode may have any other configuration added to the configuration of the above embodiment, or may be replaced with any configuration that exhibits a similar function. EXAMPLES
[0120] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these. In addition, the half-cell used in the examples of the present invention has a negative electrode mainly made of the present silicon-containing active material, and a simple evaluation is performed using metallic lithium as the counter electrode, in order to more clearly compare the cycle characteristics of the active material itself.
[0121] <Synthesis of silicon particles 1> 5000 g of commercially available silicon powder (manufactured by Kojundo Kagaku) with a silicon purity of 99.9% by mass and a volume average particle size of 3.2 μm, 2000 g of DISPERBYK9077 (manufactured by BYK Additives & Instruments, DISPERBYK is a registered trademark), and 20000 g of methyl ethyl ketone (hereinafter also referred to as "MEK") were mixed in a stirring tank and thoroughly stirred. The stirring tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere in the tank. This mixture was wet-pulverized for 1 hour using a bead mill (MSC Mill MSC220 manufactured by Nippon Coke & Engineering Co., Ltd.) to obtain a silicon-containing slurry 1 in which silicon was uniformly dispersed in the dispersion medium. The diameter of the beads in the bead mill was 0.2 mm, and the peripheral speed of the bead mill was 12 m / s. 20,000 g of the silicon-containing slurry 1 was put into a stirring tank and thoroughly stirred. The stirring tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere inside the tank. The resulting solution was wet-milled for 6.5 hours using a bead mill (MSC Mill MSC220, manufactured by Nippon Coke & Engineering Co., Ltd.) to obtain a silicon-containing slurry 2 in which silicon was uniformly dispersed in the dispersion medium. At this time, the diameter of the beads used in the bead mill was 0.1 mm, and the density of the beads was 6.0 g / cm. 3 The bead filling rate was 70%, and the peripheral speed of the bead mill was 12 m / s.
[0122] <Synthesis of silicon particles 2> 20,000 g of the silicon particle-containing slurry 1 obtained by the synthesis of the silicon particles 1 was put into a stirring tank and thoroughly stirred. The stirring tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere inside the tank. This solution was wet-milled for 6 hours using a bead mill (MSC Mill MSC220 manufactured by Nippon Coke & Engineering Co., Ltd.) to obtain nanosilicon-containing slurry 3 in which silicon was uniformly dispersed in the dispersion medium. At this time, the diameter of the beads used in the bead mill was 0.1 mm, and the density of the beads was 6.0 g / cm. 3 The bead filling rate was 70%, and the peripheral speed of the bead mill was 12 m / s.
[0123] <Synthesis of silicon particles 3> 20,000 g of the silicon particle-containing slurry 1 obtained by the synthesis of the silicon particles 1 was put into a stirring tank and thoroughly stirred. The stirring tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere inside the tank. This solution was wet-milled for 5.5 hours using a bead mill (MSC Mill MSC220 manufactured by Nippon Coke & Engineering Co., Ltd.) to obtain a nanosilicon-containing slurry 4 in which silicon was uniformly dispersed in the dispersion medium. At this time, the diameter of the beads used in the bead mill was 0.1 mm, and the density of the beads was 6.0 g / cm. 3 The bead filling rate was 70%, and the peripheral speed of the bead mill was 12 m / s.
[0124] <Synthesis of silicon particles 4> 20,000 g of the silicon particle-containing slurry 1 obtained by the synthesis of the silicon particles 1 was put into a stirring tank and thoroughly stirred. The stirring tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere inside the tank. This solution was wet-milled for 4.5 hours using a bead mill (MSC Mill MSC220 manufactured by Nippon Coke & Engineering Co., Ltd.) to obtain nanosilicon-containing slurry 5 in which silicon was uniformly dispersed in the dispersion medium. At this time, the diameter of the beads used in the bead mill was 0.1 mm, and the density of the beads was 6.0 g / cm. 3 The bead filling rate was 70%, and the peripheral speed of the bead mill was 12 m / s.
[0125] <Synthesis of silicon particles 5> 20,000 g of the silicon particle-containing slurry 1 obtained by the synthesis of the silicon particles 1 was put into a stirring tank and thoroughly stirred. The stirring tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere inside the tank. This solution was wet-milled for 4 hours using a bead mill (MSC Mill MSC220 manufactured by Nippon Coke & Engineering Co., Ltd.) to obtain a nanosilicon-containing slurry 6 in which silicon was uniformly dispersed in the dispersion medium. At this time, the diameter of the beads used in the bead mill was 0.1 mm, and the density of the beads was 6.0 g / cm. 3 The bead filling rate was 70%, and the peripheral speed of the bead mill was 12 m / s.
[0126] <Silicon particles 6> Commercially available spherical silicon particles were used as is. The particle size of the silicon particles was 50 nm. <Silicon particles 7> Commercially available spherical silicon particles were used as is. The diameter of the silicon particles was 100 nm.
[0127] <Orientation degree F(111)> 0.6 ml of the silicon-containing slurry 2 obtained by the synthesis of the silicon particles 1 was dropped onto a smooth glass substrate for XRD measurement, which was masked to create a 2 cm □ dam, and immediately dried by a spin coater at 2000 rpm for 30 seconds. The masking tape was peeled off, and θ-2θ measurement was performed by XRD in the range of 10° to 70°, and the degree of orientation F was calculated from the following formulas (1) and (2). The results are shown in Table 1.
number
number
[0128] The XRD measurement was carried out using a Cu tube target, with a tube voltage of 40 kV, a tube current of 40 mA, and an operating speed of the goniometer of 2° / min, using a SmartLab manufactured by Rigaku Corporation as the measuring device.
[0129] In the measurement of the orientation degree F(111), the silicon-containing slurry 2 was changed from the silicon-containing slurry 3 to 5, and the orientation degree F(111) of the silicon particles 2 to 5 was determined. For the silicon particles 6 and 7, 5 g of each silicon powder was mixed with 2 g of DISPERBYK 9077 (manufactured by BYK Additives & Instruments, DISPERBYK is a registered trademark) and 20 g of MEK in a stirring tank to obtain a silicon-containing slurry containing each slurry. The orientation degree F(111) of the silicon particles 6 and 7 was determined in the same manner as the silicon-containing slurry 2. The results are shown in Table 1.
[0130] <BET specific surface area> The silicon-containing slurry 2 was dried and then heated in nitrogen at 500 °C to remove the dispersant adhering to the surface of the silicon particles. The specific surface area of this powder was calculated by the BET formula using the gas adsorption - constant volume method.
[0131] In the measurement of the BET specific surface area, the silicon-containing slurry 2 was changed from the silicon-containing slurry 3 to 5, and the BET specific surface area of the silicon particles 2 to 5 was determined. The results are shown in Table 1. For the silicon particles 6 and 7, the specific surface area of the powders of the silicon particles 6 and 7 was calculated by the BET formula using the gas adsorption - constant volume method.
[0132] <Crystallite size> 2θ-θ measurement was performed by XRD. The measurement was carried out under the same conditions and using the same apparatus as the measurement of the orientation degree F. Using the full width at half maximum (FWHM) of the peak, the crystallite size of the (111) plane was calculated from the following formula (3) by the Scherrer method. The measurement angle was in the range of 10° to 70°. L = Kλ / (βcosθ) (3) In the formula (3), K is the Scherrer constant and is set to 0.9. λ is the wavelength of the X-ray used in the measurement, CuKα=1.5418 Å. β is the peak half-width in radians, θ is the Bragg angle corresponding to the (111) plane, and L is the crystallite diameter.
[0133] The crystallite sizes of silicon particles 1 to 7 were determined by the above crystallite size measurement. The results are shown in Table 1.
[0134] Synthesis Example 1 of Active Material Precursor Resin <Preparation of polysiloxane compound> (Synthesis of methyltrimethoxysilane condensate (a1)) A reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube, and a nitrogen gas inlet was charged with 1,421 parts by mass of methyltrimethoxysilane (hereinafter, referred to as "MTMS") and heated to 60° C. Next, a mixture of 0.17 parts by mass of isopropyl acid phosphate ("Phoslex A-3" manufactured by SC Organic Chemical Co., Ltd.) and 207 parts by mass of deionized water was dropped into the reaction vessel over a period of 5 minutes, and the mixture was stirred at a temperature of 80° C. for 4 hours to carry out a hydrolysis and condensation reaction of MTMS. The condensate obtained by the hydrolysis and condensation reaction was distilled at a temperature of 40 to 60°C and under a reduced pressure of 40 to 1.3 kPa. The phrase "under a reduced pressure of 40 to 1.3 kPa" means that the reduced pressure condition at the start of methanol distillation is 40 kPa, and the pressure is finally reduced to 1.3 kPa. The same applies to the following description. By removing the methanol and water produced during the reaction, 1,000 parts by mass of a liquid containing a condensate of MTMS having a number average molecular weight of 1,000 to 5,000 (hereinafter also referred to as "a1"). The content of the active ingredient in the obtained liquid was 70% by mass. The effective component is calculated by dividing the theoretical yield (parts by mass) when all methoxy groups of a silane monomer such as MTMS undergo a condensation reaction by the actual yield (parts by mass) after the condensation reaction, i.e., [theoretical yield (parts by mass) when all methoxy groups of a silane monomer undergo a condensation reaction / actual yield (parts by mass) after the condensation reaction].
[0135] <Production of Curable Resin Composition> A reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube, and a nitrogen gas inlet was charged with 150 parts by mass of butanol (hereinafter also referred to as "BuOH"), 105 parts by mass of phenyltrimethoxysilane (hereinafter also referred to as "PTMS"), and 277 parts by mass of dimethyldimethoxysilane (hereinafter also referred to as "DMDMS"), and the temperature was raised to 80°C. Next, at the same temperature, a mixture containing 21 parts by mass of methyl methacrylate (hereinafter also referred to as "MMA"), 4 parts by mass of butyl methacrylate (hereinafter also referred to as "BMA"), 3 parts by mass of butyric acid (hereinafter also referred to as "BA"), 2 parts by mass of methacryloyloxypropyltrimethoxysilane (hereinafter also referred to as "MPTS"), 3 parts by mass of BuOH, and 0.6 parts by mass of butylperoxy-2-ethylhexanoate (hereinafter also referred to as "TBPEH") was dropped into the reaction vessel over 6 hours. After the dropwise addition was completed, the mixture was further reacted at the same temperature for 20 hours to obtain an organic solvent solution of a vinyl polymer (a2) having a number average molecular weight of 10,000 and having a hydrolyzable silyl group.
[0136] Next, a mixture of 0.04 parts by mass of isopropyl acid phosphate ("Phoslex A-3" manufactured by SC Organic Chemical Co., Ltd.) and 112 parts by mass of deionized water was added dropwise over a period of 5 minutes, and the mixture was stirred at the same temperature for a further 10 hours to cause a hydrolysis condensation reaction, thereby obtaining a liquid containing a composite resin in which the hydrolyzable silyl group of the vinyl polymer (a2) and the hydrolyzable silyl group and silanol group of the polysiloxane derived from the PTMS and DMDMS were bonded together. Next, 472 parts by mass of the MTMS condensate (a1) obtained by the above synthesis and 80 parts by mass of deionized water were added to this liquid, and the mixture was stirred at the same temperature for 10 hours to cause a hydrolysis condensation reaction, and the produced methanol and water were removed by distillation under the same conditions as in Synthesis Example 1. Next, 250 parts by mass of BuOH was added, and 1,000 parts by mass of a curable resin composition with a non-volatile content of 60.1% by mass was obtained.
[0137] <Preparation of negative electrode active material> Examples 1 to 3 The silicon particles 1 to 3 that had completed the above property evaluation were mixed in an agitation tank in an amount of 5000 g, 2000 g of DISPERBYK9077 (manufactured by BYK Additives & Instruments, DISPERBYK is a registered trademark), and 20000 g of methyl ethyl ketone (hereinafter also referred to as "MEK"), and the mixture was thoroughly mixed. The agitation tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere in the tank. The silicon-containing slurry, the curable resin composition, and the phenolic resin (Sumitomo Bakelite, Sumilite Resin PR-53570) were mixed so that the SiOC / C / Si ratio was 10 / 40 / 50, calculated based on the composition after firing, and charged into a three-necked separable flask. One neck was covered, and a nitrogen inlet tube and a solvent trap were connected to the remaining two necks. Nitrogen was introduced into the flask, and the flask was heated to 120°C in an oil bath while stirring the mixture with a magnetic stirrer, and the solvent was distilled off until the viscosity reached a level at which the stirrer no longer moved. The mixture was then cooled to room temperature to obtain a dried resin material, which is a precursor to be fired. The dried resin material, which is a precursor to be fired, was then fired in a nitrogen atmosphere at a temperature of 1050°C for 6 hours to obtain a black solid material. The obtained black solid material was pulverized with a planetary ball mill to obtain negative electrode active materials 1 to 3.
[0138] Comparative Examples 1 to 4 Negative electrode active materials 4 to 7 were obtained in the same manner as in Examples 1 to 3 using silicon powders 4 to 7.
[0139] [Charge / discharge measurement evaluation] A mixed slurry containing 80% by mass of the negative electrode active materials 1 to 7, 10% by mass of acetylene black as a conductive assistant, and 10% by mass of a mixture of CMC and SBR as a binder was prepared and formed on a copper foil. It was then dried under reduced pressure at 110°C and a Li metal foil was used as the counter electrode to prepare a half cell. A charge / discharge test was performed on this half cell using a secondary battery charge / discharge measuring device (manufactured by Hokuto Co., Ltd.) with a cutoff voltage range of 0.005 to 1.5 V and a current value equivalent to 0.1 C. The results of this test were used to calculate the capacity loss rate after 20 cycles using the following formula: Capacity decrease rate after 20 cycles = (discharge capacity at 21st cycle) / (discharge capacity at 2nd cycle) x 100
[0140] The results of the capacity reduction rates after 20 cycles of the negative electrode active materials 1 to 7 obtained by the above method are summarized in Table 1.
[0141] [Table 1]
[0142] <Synthesis of silicon particles 8 to 10> 5000 g of commercially available silicon powder (manufactured by Kojundo Kagaku) with a silicon purity of 99.9% by mass and a volume average particle size of 3.2 μm, 2000 g of DISPERBYK9077 (manufactured by BYK Additives & Instruments, DISPERBYK is a registered trademark), and 20000 g of methyl ethyl ketone (hereinafter also referred to as "MEK") were mixed in a stirring tank and thoroughly stirred. The stirring tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere in the tank. This mixture was wet-pulverized for 1 hour using a bead mill (MSC Mill MSC220 manufactured by Nippon Coke & Engineering Co., Ltd.) to obtain a silicon-containing slurry 7 in which silicon was uniformly dispersed in the dispersion medium. The diameter of the beads in the bead mill was 0.2 mm, and the peripheral speed of the bead mill was 12 m / s. The silicon-containing slurry 7 was put into a stirring tank in an amount of 20,000 g and thoroughly stirred. The stirring tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere inside the tank. The resulting solution was wet-pulverized using a bead mill (MSC Mill MSC220 manufactured by Nippon Coke & Engineering Co., Ltd.) for 6.75 hours for silicon particles 8, 7 hours for silicon particles 9, and 6.25 hours for silicon particles 10, to obtain silicon-containing slurries containing silicon particles 8, 9, or 10 in which silicon is uniformly dispersed in a dispersion medium. In each case, the diameter of the beads used in the bead mill was 0.1 mm, and the density of the beads was 6.0 g / cm. 3 The bead filling rate was 70%, and the peripheral speed of the bead mill was 12 m / s. The degree of orientation F(111) of silicon particles 8 to 10 was all 0.2 or more.
[0143] Examples 4 to 6 Negative electrode active materials 8 to 10 were obtained in the same manner as in Examples 1 to 3 using the silicon particles 8 to 10 obtained above. The degree of orientation of silicon particles, BET specific surface area, crystallite size, and average particle size (D50) of each of the obtained negative electrode active materials were measured based on the following <Measurement of the degree of orientation of silicon particles in the negative electrode active material>, <BET specific surface area of the negative electrode active material powder>, <Crystallite size of the negative electrode active material powder>, and <Measurement of the average particle size (D50) of the negative electrode active material powder>. The results are shown in Table 2.
[0144] <Synthesis of silicon particles 11 and 12> 5000 g of commercially available silicon powder (manufactured by Kojundo Kagaku) with a silicon purity of 99.9% by mass and a volume average particle size of 3.2 μm, 2000 g of DISPERBYK9077 (manufactured by BYK Additives & Instruments, DISPERBYK is a registered trademark), and 20000 g of methyl ethyl ketone (hereinafter also referred to as "MEK") were mixed in a stirring tank and thoroughly stirred. The stirring tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere in the tank. This mixture was wet-pulverized for 1 hour using a bead mill (MSC Mill MSC220 manufactured by Nippon Coke Engineering Co., Ltd.) to obtain a silicon-containing slurry 8 in which silicon was uniformly dispersed in the dispersion medium. The diameter of the beads in the bead mill was 0.2 mm, and the peripheral speed of the bead mill was 12 m / s. 20,000 g of the silicon-containing slurry 8 was put into a stirring tank and thoroughly stirred. The stirring tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere inside the tank. The resulting solution was wet-pulverized using a bead mill (MSC Mill MSC220, manufactured by Nippon Coke & Engineering Co., Ltd.) for 3.5 hours for silicon particles 11 and 2.5 hours for silicon particles 12, respectively, to obtain silicon-containing slurries containing silicon particles 11 or 12 in which silicon is uniformly dispersed in a dispersion medium. In both cases, the diameter of the beads used in the bead mill was 0.1 mm, and the density of the beads was 6.0 g / cm. 3 The bead filling rate was 70%, and the peripheral speed of the bead mill was 12 m / s. The degree of orientation F(111) of the silicon particles 11 and 12 was both less than 0.2.
[0145] Comparative Examples 5 and 6 The silicon particles 11 and 12 obtained above were used to obtain negative electrode active materials 11 to 12 in the same manner as in Examples 1 to 3. The properties of the obtained negative electrode active materials were measured in the same manner as in Examples 4 to 6. The charge / discharge evaluation was carried out in the same manner as in the above [Evaluation of charge / discharge measurement] using the obtained negative electrode active materials 11 to 12. The results are shown in Table 2.
[0146] <Measurement of the degree of orientation of silicon particles in negative electrode active material> The negative electrode active material powder obtained above was filled on the ground glass surface using a glass sample holder for XRD powder measurement, so that the surface height of the sample holder and the surface height of the sample powder were the same. θ-2θ measurement was performed by XRD in the range of 10° to 70°, and the orientation degree F was calculated from the above formulas (1) and (2). The measurement conditions and the measurement device for XRD were the same as those described above.
[0147] <BET specific surface area of negative electrode active material powder> The specific surface area of the negative electrode active material powder obtained above was calculated by the BET equation according to the gas adsorption method-constant volume method.
[0148] <Measurement of the average particle size (D50) of negative electrode active material powder> The average particle size (D50) of the negative electrode active material powder obtained above was measured using a laser diffraction particle size distribution meter (Mastersizer LMS3000 manufactured by Spectris Inc.) under the same conditions as those for the particle size measurement of the silicon particles, using distilled water as a measurement solvent. D50 was measured five or more times under the above conditions, and the CV value (standard deviation / average value) of D50 was 5% or less for five consecutive measurements, confirming the stability of the measurement, and then the D50 value was calculated.
[0149] <Crystallite diameter of negative electrode active material powder> The negative electrode active material powder obtained above was subjected to 2θ-θ measurement by XRD using a SmartLab manufactured by Rigaku Corporation. Using the full width at half maximum (FWHM) of the peak, the crystallite size of the (111) plane was calculated from the following formula (3) by the Scherrer method. The measurement angle was in the range of 10° to 70°. L = Kλ / (βcosθ) (3) In the formula (3), K is a shape factor and is set to 0.9. λ is the wavelength of the X-ray used in the measurement, CuKα=1.5418 Å. β is the peak half-width in radians, θ is the Bragg angle corresponding to the (111) plane, and L is the crystallite diameter.
[0150] The capacity loss rates after 20 cycles of the negative electrode active materials 8 to 12 obtained by the above method were measured by the same method as above. The results are shown in Table 2.
[0151] [Table 2]
[0152] From the measurement of the capacity loss rate after 20 cycles of the half cell, it was found that the smaller the capacity loss rate after 20 cycles, the longer the life of the half cell, indicating excellent cycle properties. As is clear from the results in Tables 1 and 2 above, the secondary battery using the present silicon particles as the negative electrode active material has a small capacity loss rate after 20 cycles, and the resulting secondary battery has excellent cycle properties.
Claims
1. Silicon particles having a degree of orientation of the (111) plane, F(111), of 0.2 or more as determined by the Lotgering method in X-ray diffraction.
2. BET specific surface area is 80m 2 The silicon particles according to claim 1, wherein the molecular weight is 1 / g or more.
3. The silicon particles according to claim 2, having a crystallite diameter calculated by the Scherrer method of 5 nm to 14 nm.
4. A silicon-containing active material comprising the silicon particles according to claim 1 .
5. 5. The silicon-containing active material according to claim 4, wherein the degree of orientation of the (111) plane of silicon particles, F(111), obtained by the Lotgering method in X-ray diffraction of the silicon-containing active material is 0.03 or more.
6. BET specific surface area is 50m 2 The silicon-containing active material according to claim 4 or 5, wherein the molecular weight is 1 / g or less.
7. 6. The silicon-containing active material according to claim 4, wherein the volume average particle size is from 2 μm to 20 μm.
8. 6. The silicon-containing active material according to claim 4, wherein the crystallite size of silicon in the silicon-containing active material is 40 nm or less.
9. 6. The silicon-containing active material according to claim 4, which contains a matrix phase containing silicon, oxygen and carbon as main components.
10. A negative electrode active material for a secondary battery, comprising the silicon-containing active material according to claim 4 or 5.
11. A negative electrode comprising the negative electrode active material for a secondary battery according to claim 10.
12. A secondary battery comprising the negative electrode according to claim 11.
Citation Information
Patent Citations
Silicon nanoparticles, active material for negative electrode of non-aqueous secondary battery including the same, and secondary battery
JP2021114483A
Silicon or silicon alloy, composite active material for lithium secondary battery containing the same, and manufacturing method thereof
JP2021180124A